Software Testing with the approach of Blackbox Testing on the Academic Information System - S Supriyono (IJISTECH (International Journal of Information System and Technology), 2020)
SIAKAD is a website based information system assessment application that holds academic data of an educational institution. SIAKAD SDIT Robbani was created to help the assessment process of students, both in the form of public and religious subjects. With this investigation is expected to facilitate the assessment process at the school Rabbani. For that, testing is required to know whether the system can run as expected or not. Software Testing was conducted using black-box testing. The software testing method uses a Boundary Value Analysis (BVA) because the assessment has the minimum and maximum constraints of an inputted value. The test results show the scoring system has not been able to fulfil expectations because there is no limit value so the random value will remain stored by the system. This can result in incorrect information generated by the SIAKAD.